2009
DOI: 10.1136/pgmj.2008.068635
|View full text |Cite
|
Sign up to set email alerts
|

Cold damage to the extremities: frostbite and non-freezing cold injuries

Abstract: The treatment of cold injuries to the periphery has advanced substantially in the last 10 years and optimal outcomes are only likely to be achieved if a multidisciplinary team uses the full range of diagnostic and treatment modalities that are now available. The internet and satellite phones with digital images allow immediate access by patients from remote geographical locations to hospital based specialists who can assess cold injuries and advise on early field care. The severity of frostbite injuries can no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
164
0
13

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(178 citation statements)
references
References 23 publications
1
164
0
13
Order By: Relevance
“…Previous studies found elevated levels of prostaglandin and thromboxane in clear frostbite blister fluid. 13,23 These metabolites of arachidonic acid have been heavily implicated as mediators of progressive dermal ischemia in burn, frostbite, or ischemia/reperfusion injuries. 24 Debridement of clear blisters is included in the protocol as a means to remove these inflammatory agents and improve wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies found elevated levels of prostaglandin and thromboxane in clear frostbite blister fluid. 13,23 These metabolites of arachidonic acid have been heavily implicated as mediators of progressive dermal ischemia in burn, frostbite, or ischemia/reperfusion injuries. 24 Debridement of clear blisters is included in the protocol as a means to remove these inflammatory agents and improve wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Severity of frostbite was categorized into superficial (1st and 2nd degree) or deep (3rd and 4th degree) ( Figure 1). 1,[10][11][12][13] Distribution of predisposing factors were compared between superficial and deep injuries using student t-tests for continuous variables and chi-squared or Fisher's exact tests for categorical variables. Patient encounters were reviewed to determine if the protocol was followed (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Skin-surface temperature is highly dependent on blood circulation in the outer millimetres of the skin, which is controlled by a complex autonomic regulatory system as well as local factors. There are although research findings underpinning the fact that nerve function governing vessel diameter is essential in terms of regulation of peripheral microcirculation as part of the pathophysiology of cold injuries [5]. …”
Section: Introductionmentioning
confidence: 99%